Multisubunit RNA polymerases IV and V: Purveyors of non-coding RNA for plant gene silencing - Haag, J.R.; Pikaard, C.S.
In all eukaryotes, nuclear DNA-dependent RNA polymerases I, II and III synthesize the myriad RNAs that are essential for life. Remarkably, plants have evolved two additional multisubunit RNA polymerases, RNA polymerases IV and V, which orchestrate non-coding RNA-mediated gene silencing processes affecting development, transposon taming, antiviral defence and allelic crosstalk. Biochemical details concerning the templates and products of RNA polymerases IV and V are lacking. However, their subunit compositions reveal that they evolved as specialized forms of RNA polymerase II, which provides the unique opportunity to study the functional diversification of a eukaryotic RNA polymerase family.
Keywords: NA DIRECTED RNA POLYMERASE; DNA DIRECTED RNA POLYMERASE III; RNA POLYMERASE; RNA POLYMERASE II; RNA POLYMERASE IV; RNA POLYMERASE V; UNCLASSIFIED DRUG; UNTRANSLATED RNA